Impact of perceived usefulness, ease of use, and privacy & security on QRIS adoption: mediating role of behavioral intention - Kurnia, Elsa; Yolanda, Mike (Marketing Management Studies, 2024)
This study aims to analyze the effect of Perceived Usefulness, Perceived Ease of Use, Privacy & Security on QRIS Use with Behavioral Intention as an Intervening Variable in State University Students in Padang City. The research focused on State University students residing in Padang City. A total of 190 respondents participated in the study, providing data via online questionnaires. Structural Equation Modeling (SEM) utilizing SmartPLS4 software was employed for data analysis. The findings revealed that: (1) Behavioral Intention significantly influences the utilization of QRIS among State University students in Padang City. (2) Perceived Usefulness significantly impacts the Behavioral Intention of State University students in Padang City. (3) Perceived Ease Of Use also significantly affects the Behavioral Intention of State University students in Padang City. (4) Additionally, Privacy & Security demonstrate a significant influence on the Behavioral Intention of State University students in Padang City.